2020
DOI: 10.1016/j.ekir.2020.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CKD Progression on Cardiovascular Disease Risk in a Contemporary UK Cohort of Individuals With Diabetes

Abstract: Introduction: It remains unclear whether an increased progression rate of chronic kidney disease (CKD) adds predictive information regarding cardiovascular disease (CVD) risk. The aim of this study was to evaluate the association between CKD progression, based on estimated glomerular filtration rate (eGFR) slope estimates and the risk for CVD. Methods: We compared the updated eGFR slope calculated over multiple overlapping 2-year periods and the updated mean eGFR. Incident CKD subjects were selected from a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…First, it is plausible that in these patients with DM of a short duration, they had relatively earlier stages of CKD; early CKD increases the risk of ischemic stroke through its concurrence with other predisposing factors such as hypertension, most of which were already adjusted for in our analyses. Similar findings are reported recently; Cabrera et al [ 36 ], using clinical practice data from United Kingdom, showed that CKD did not alter the risk of IS among a large cohort of patients with DM. Oh and colleagues also demonstrated that there was no association between lower estimated glomerular filtrate rate (eGFR) levels and the risk of HS in a population-based cohort of Korean patients [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…First, it is plausible that in these patients with DM of a short duration, they had relatively earlier stages of CKD; early CKD increases the risk of ischemic stroke through its concurrence with other predisposing factors such as hypertension, most of which were already adjusted for in our analyses. Similar findings are reported recently; Cabrera et al [ 36 ], using clinical practice data from United Kingdom, showed that CKD did not alter the risk of IS among a large cohort of patients with DM. Oh and colleagues also demonstrated that there was no association between lower estimated glomerular filtrate rate (eGFR) levels and the risk of HS in a population-based cohort of Korean patients [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is widely reported in the literature that patients with chronic renal failure have an increased risk of CCV events and it is interesting to see that even small increases in creatinine help identify patients with an heightened risk of MACE [31][32][33]. In our study, the GFR shows the highest OR (3.6) compared to all the other risk factors, leaving no doubt that for patients with renal insufficiency interventions on the other risk factors are a priority.…”
Section: Therapeutic Possibilities and Cardiovascular Riskmentioning
confidence: 52%
“…Major shared risk factors between CKD and CVD include diabetes and hypertension. Diabetes is the leading cause of CKD and dialysis in many countries [30] and considerably increases the risk of various CVD subtypes such as myocardial infarction, stroke, and heart failure [31]. Hypertension is another major cause of CKD and is the leading cause of CVD, especially stroke [32,33].…”
Section: Shared Risk Factors Between Ckd and Cvdmentioning
confidence: 99%